Safety and efficacy of l‐cysteine monohydrochloride monohydrate produced by fermentation using Escherichia coli KCCM 80109 and Escherichia coli KCCM 80197 for all animal species. (30th April 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of l ‐cysteine monohydrochloride monohydrate produced by fermentation using two non‐genetically modified strains of Escherichia coli K12 ( E. coli KCCM 80109 and E. coli KCCM 80197) as a flavouring additive for all animal species. No safety concerns are derived from the use of these strains as production strains of the additive. The FEEDAP Panel concludes that the use of l ‐cysteine hydrochloride monohydrate produced by E. coli KCCM 80109 and KCCM 80197 at concentrations up to 25 mg/kg complete feed is safe for the target species, for the consumer and for the environment. The product is proposed to be classified as respiratory irritant; however, exposure by inhalation is unlikely. Based on the results of the studies provided, it should be classified as skin irritant and that it causes serious eye damage. l ‐Cysteine hydrochloride monohydrate is not a dermal sensitiser. Since l ‐cysteine hydrochloride monohydrate is used in food as flavourings, it is to be expected that it can provide a similar function in feed and no further demonstration of efficacy is necessary when used at concentrations up to 25 mg/kg complete feed and the corresponding concentration in water.